APPLIED RESEARCH OF TRANSPORT INFRASTRUCTURE FOR SLOVAK CAPITAL DEMAND - Puskelova, Maria; Ondrasikova, Lubica (European Scientific Journal, ESJ, 2014)
Bratislava as the capital of Slovakia is very important knot in Slovak business or tourism. That is why transport infrastructure plays very important role. The increase role of green bicycle transportation and the demand for sustainable tourism require building corresponding infrastructure for urban cyclists, cycle commuters and cycle tourists. The priority of government should be to develop this industry. They should also generate pressure on private entrepreneurs operating public transportation to mind the safety of their clients. It is also related to innovation and improving the quality of services that they provide.